FOLK ART DIGITIZATION MANAGEMENT FRAMEWORK - Imsong, Talisenla; J.Karthikeyan; R.Vasanthan; Gupta, Dr. Peeyush Kumar; Dzüvichü, Khriereizhünuo; Parmar, Yuvraj (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Folk art has to be preserved and disseminated in a digital age within a cultural framework, with the proper use of technology and enduring nature. The Folk Art Digitisation Management Framework (FADMF) is a model, which is proposed in this study. It is designed to assist in digitising, managing and sharing traditional arts. The approach is founded on ideas of different fields, combining observational study, archive practices and digital preservation methods. It emphasizes the need to work collectively with artists, groups and cultural institutions to ensure that the digitisation process is real and open to all. The research combines a combination of surveys, historical content and interviews with stakeholders to determine the various methods of digitisation of folk art and the challenges involved. FADMF consists of three major components: (1) Conceptual Model, which is used to describe metadata standards and content organisation; (2) Workflow Design, used to design how to acquire, catalogue, store, and access content; and (3) Stakeholder Roles, which describes the roles of policymakers, technologists, and people that care about culture. A test application demonstrates the ways in which the framework can be applied and compares the success of the framework to that of other digital heritage models. He found that the information is more valid, easier to access, and more socially acceptable. The paper also discusses infrastructure requirements, data management, and policy implications that will contribute to digital preservation for future stability.